Research Progress on Electrochemical Recycled Activated Carbon - Zhao, Derun; Zhang, Yaozong (International Journal of Materials Science and Technology Studies, 2025)
Activated carbon (AC) is widely used in water treatment and environmental pollution control due to its excellent adsorption properties. However, the regeneration of saturated AC remains a critical challenge. As an efficient and environmentally friendly regeneration technology, electrochemical regeneration drives redox reactions through applied electric fields to degrade adsorbed pollutants and restore AC’s adsorption capacity. This paper reviews the mechanisms of electrochemical AC regeneration, including direct electron transfer, ·OH radical oxidation, and electrochemical desorption. It explores how key parameters such as electrode materials, current density, electrolyte type, and pH value affect regeneration efficiency. Research demonstrates that electrochemical regeneration offers advantages like low energy consumption, minimal secondary pollution, and high regeneration rates, making it particularly suitable for regenerating saturated AC with high-concentration organic pollutants. Future research should focus on optimizing reactor designs, developing stable electrode materials, and exploring application potential in complex real-world wastewater systems.